Plywood containing modal fibers and production process thereof

By introducing modal fibers into plywood and using improved plywood technology, the problem of insufficient strength and processing performance of plywood is solved, the recycling of resources and environmental protection benefits are achieved, and the overall performance and weather resistance of plywood are improved.

CN119116087AActive Publication Date: 2024-12-13NANJING FORESTRY UNIV
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411047670.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-01
Publication Date
2024-12-13
Estimated Expiration
2044-08-01

AI Technical Summary

Technical Problem

Traditional plywood has shortcomings in strength, stability, processing performance and weather resistance, and the scrap materials resources generated during the garment making process are seriously wasted, which affects environmental protection.

Method used

Modal fibers are introduced as reinforcement materials and processed through improved glue technology and process, including crushing of wood materials, coupling agent or steam blasting treatment, layered alternate laying of phenolic resin glue, cold pressing treatment and vibration aids to ensure fibers and wood Uniform bonding of materials.

Benefits of technology

It significantly improves the physical and processing properties of plywood, reduces material losses and tool wear, improves the overall strength, stability and durability of the board, and realizes the recycling of resources and environmental protection benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004973953440000061
    Figure BDA0004973953440000061
  • Figure BDA0004973953440000071
    Figure BDA0004973953440000071
Patent Text Reader

Abstract

The invention discloses plywood containing modal fibers and a production process thereof. The production process comprises the following steps: crushing wood into particles of not more than 30 meshes; spraying a coupling agent to the modal fibers or performing steam explosion treatment; the wood particles and the modal fibers are alternately laid in a layered mode, and phenolic resin glue is sprayed on each layer of laid wood particles and modal fibers; the cold pressing pressure is controlled to be 1.2-1.8 MPa, the pressing time is set to be 12-24 hours, the pressing environment temperature is 20-25 DEG C, the humidity is 45%-55%, and vibration assistance is implemented in the pressing process; and after pressing is completed, pressure is relieved, and the plywood is taken out. The production technology of the plywood containing the modal fibers has the remarkable beneficial effects that the strength and stability of the plywood are improved, the machining performance is improved, the durability and weather resistance are improved, and effective utilization of resources is achieved. Due to the effects, the plywood has wide application prospects and market competitiveness in the plywood production field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plywood production technology, and in particular relates to a plywood containing modal fibers and a production technology thereof. Background Art

[0002] With the continuous advancement of science and technology, plywood, as a widely used building material, plays an important role in many fields such as construction, furniture manufacturing, decoration and decoration. However, traditional plywood still needs to be improved in terms of strength and stability, and processing performance, durability and weather resistance also need to be further optimized. In order to solve these problems, we continue to explore new reinforcing materials in order to improve the comprehensive performance of plywood. Among many potential reinforcing materials, modal fiber has attracted much attention due to its softness and good hygroscopicity. Modal fiber is a new type of fiber material made by mixing wood pulp fiber and cotton fiber. It not only has the softness and comfort of natural fiber, but also has the durability of synthetic fiber. In the garment industry, modal fiber is favored for its excellent elasticity and recovery. However, the scraps generated in the garment making process are often regarded as waste, which not only causes a waste of resources, but also increases the environmental burden. The present invention introduces modal fiber into plywood manufacturing, aiming to investigate whether it is suitable for plywood through the reinforcing effect of fiber. At the same time, it is investigated whether the addition of modal fiber can also improve the processing performance of plywood, making it smoother during cutting, drilling and other processing processes, reducing material loss and tool wear. In addition, after adding modal fiber, whether there is an impact on the durability and weather resistance of plywood, verify its stability in harsh environments. At present, the applicant has found that the application of modal fiber faces some challenges, mainly because the cohesion between its fibers is relatively small, and it is easy to produce pilling during friction, which will have an adverse effect on the fusion of fiber and wood material. In order to overcome this problem, the present invention has been innovated in fiber processing technology, and an improved gluing technology has been adopted to ensure that modal fiber can be evenly dispersed in plywood and form a good combination with wood material. This combination not only improves the overall performance of the board, but also effectively utilizes the scraps generated in the clothing process, realizes the recycling of resources, reduces production costs, and also contributes to environmental protection. Summary of the invention

[0003] Technical problem solved: In view of the above technical problems, the present invention provides a plywood containing modal fiber and a production process thereof, and successfully introduces modal fiber as a reinforcing material, which not only significantly improves the physical properties and processing properties of the plywood, but also solves the problem of waste of scraps in the garment industry.

[0004] Technical solution: A production process of plywood containing modal fiber, the preparation steps are as follows: preparation of wood material: crushing wood into particles not exceeding 30 meshes, and controlling the moisture content of wood to be between 8% and 12%; preparation of modal fiber: spraying coupling agent on modal fiber or using steam explosion treatment, the amount of coupling agent used is 0.1% to 2.0% of the mass of modal fiber; embryo assembly and glue coating: according to the mass ratio of wood material to modal fiber (90-70): (30-10), wood particles and modal fiber are alternately laid in layers, and phenolic resin glue is sprayed on each layer, and the amount of phenolic resin glue is 70-100 kg / m 3 ; Cold pressing treatment: The cold pressing pressure is controlled between 1.2-1.8MPa, the pressing time is set to 12-24 hours, the pressing environment temperature is 20-25℃, the humidity is 45%-55%, and vibration assistance is implemented during the pressing process; Pressure relief and removal: After the pressing is completed, the pressure is relieved and the plywood is removed.

[0005] Preferably, the coupling agent is an aluminate coupling agent.

[0006] Preferably, the phenolic resin adhesive is LPF resin adhesive.

[0007] The steam explosion treatment method is as follows: the modal fiber is crushed to less than 30 meshes, soaked in 2wt.% NaOH solution, and then the modal fiber is placed in a closed steam explosion chamber, the steam pressure is controlled at 1.0-7.0MPa, and treated in high temperature and high pressure steam for 15-40 seconds; the pressure is completely released within 0.00875 seconds, and ethanol is used for cleaning.

[0008] Preferably, the steam pressure is maintained for 4 to 5 seconds after rising to 7.0 MPa.

[0009] Preferably, the mass ratio of the above-mentioned wood material:modal fiber is 4:1.

[0010] Preferably, the amount of the LPF resin adhesive is 75Kg / m 3 .

[0011] Preferably, the initial stage of the above-mentioned cold pressing: starting pressing with a pressure of 0.5-0.8 MPa, lasting for 20%-30% of the total pressing time; the pressure increasing stage: increasing the pressure to 1.4-1.5 MPa, lasting for 40%-50% of the total pressing time; the final pressing stage: during the remaining part of the pressing time, the pressure is increased to 1.6 MPa.

[0012] Preferably, the parameters of the cold pressing treatment are: the pressure is controlled at 1.5 MPa, the pressing time is set to 18 hours, the ambient temperature is controlled at 22-24° C., and the humidity is controlled at 48%-52%.

[0013] Preferably, the frequency of the above-mentioned vibration: micro-vibration is applied in the pressure increase stage and the final pressure stage, and the vibration frequency is controlled between 10-50 Hz; vibration amplitude: the vibration amplitude of micro-vibration is controlled between 0.1-0.5 mm; vibration time: micro-vibration is applied within the last 10-15 minutes of each pressing stage.

[0014] The plywood containing modal fiber is produced by the production process.

[0015] Beneficial effects: First, the present invention ensures the quality and stability of the base material by strictly controlling the particle size and moisture content of the wood material, laying a solid foundation for the subsequent gluing process. At the same time, the modal fiber is treated with a coupling agent or steam explosion, which effectively improves the interface compatibility between the fiber and the wood material and the adhesive, and enhances the bonding force between them.

[0016] Secondly, the present invention adopts a specific assembly and gluing method to lay wood particles and modal fibers in layers alternately, and spray phenolic resin glue on each layer. This structure not only allows the fibers and wood materials to be distributed more evenly, but also improves the overall strength and stability of the board. In addition, the selected LPF resin adhesive has good water resistance and weather resistance, further enhancing the durability of the plywood.

[0017] Furthermore, through the optimized cold pressing process, including precise control of pressure, time, ambient temperature and humidity, and the implementation of vibration assistance during the pressing process, the fibers and wood particles inside the board are more closely combined, improving the density and mechanical properties of the board. This vibration assistance also helps to discharge bubbles and excess glue inside the board, thereby obtaining a more uniform and high-quality plywood.

[0018] Finally, in the preferred embodiment of the present invention, the performance of plywood is optimized by finely adjusting various process parameters, such as the mass ratio of wood material to modal fiber, the amount of LPF resin adhesive, and the parameters of each stage of cold pressing treatment. These optimization measures not only improve production efficiency, but also reduce production costs, while ensuring the excellent performance of plywood.

[0019] In summary, the plywood production process containing modal fiber provided by the present invention has significant beneficial effects, including improving the strength and stability of the board, improving the processing performance, enhancing the durability and weather resistance, and realizing the effective utilization of resources, etc. These effects together make the present invention have broad application prospects and market competitiveness in the field of plywood production. DETAILED DESCRIPTION

[0020] The present invention is described in more detail below through examples.

[0021] Example 1

[0022] Preparation of wood materials: The wood was crushed into 25 mesh particles and the moisture content was controlled at 10wt.%.

[0023] Modal fiber preparation: treated with aluminate coupling agent, the amount used is 0.5wt.% of the fiber mass.

[0024] Embryo assembly and gluing: The mass ratio of wood material to modal fiber is 80:20. The wood particles and modal fibers are laid alternately in layers. Each layer is sprayed with phenolic resin glue. The amount of phenolic resin glue (LPF resin adhesive) is 80Kg / m 3 .

[0025] Cold pressing treatment: pressure 1.5MPa, time 18 hours, ambient temperature 23℃, humidity 50%. Micro-vibration was applied during the pressure increase and final pressure stages, with a frequency of 30 Hz and an amplitude of 0.3 mm, and the time was the last 15 minutes of each stage.

[0026] Example 2

[0027] Preparation of wood materials: The wood was crushed into 25 mesh particles and the moisture content was controlled at 10wt.%.

[0028] Preparation of modal fiber: steam explosion treatment was used to crush the modal fiber to less than 30 mesh, and then the modal fiber was soaked in 2wt.% NaOH solution. The modal fiber was then placed in a closed steam explosion chamber with a steam pressure of 5.0 MPa and a treatment time of 30 seconds. The pressure was completely released within 0.00875 seconds, and the fiber was washed with ethanol.

[0029] Embryo assembly and gluing: The mass ratio of wood material to modal fiber is 80:20. The wood particles and modal fibers are laid alternately in layers. Each layer is sprayed with phenolic resin glue. The amount of phenolic resin glue (LPF resin adhesive) is 80Kg / m 3 .

[0030] Cold pressing treatment: pressure 1.5MPa, time 18 hours, ambient temperature 23℃, humidity 50%. Micro-vibration was applied during the pressure increase and final pressure stages, with a frequency of 30 Hz and an amplitude of 0.3 mm, and the time was the last 15 minutes of each stage.

[0031] Example 3

[0032] Preparation of wood materials: The wood is crushed into 30 mesh particles and the moisture content is controlled at 8%.

[0033] Modal fiber preparation: treated with aluminate coupling agent, the amount used is 0.5wt.% of the fiber mass.

[0034] Embryo assembly and gluing: The mass ratio of wood material to modal fiber is 75:25. The wood particles and modal fibers are laid alternately in layers. Each layer is sprayed with phenolic resin glue. The amount of phenolic resin glue is 75Kg / m 3 .

[0035] Cold pressing treatment: pressure 1.6MPa, time 20 hours, ambient temperature 22℃, humidity 48%. Micro-vibration was applied during the pressure increase and final pressure stages, with a frequency of 30 Hz and an amplitude of 0.3 mm, and the time was the last 15 minutes of each stage.

[0036] Example 4

[0037] Preparation of wood materials: The wood is crushed into 30 mesh particles and the moisture content is controlled at 8%.

[0038] Preparation of modal fiber: steam explosion treatment was used to crush the modal fiber to less than 30 mesh, and then the modal fiber was soaked in 2wt.% NaOH solution. The modal fiber was then placed in a closed steam explosion chamber with a steam pressure of 5.0 MPa and a treatment time of 30 seconds. The pressure was completely released within 0.00875 seconds, and the fiber was washed with ethanol.

[0039] Embryo assembly and gluing: The mass ratio of wood material to modal fiber is 75:25. The wood particles and modal fibers are laid alternately in layers. Each layer is sprayed with phenolic resin glue. The amount of phenolic resin glue is 75Kg / m 3 .

[0040] Cold pressing treatment: pressure 1.6MPa, time 20 hours, ambient temperature 22℃, humidity 48%. Micro-vibration was applied during the pressure increase and final pressure stages, with a frequency of 30 Hz and an amplitude of 0.3 mm, and the time was the last 15 minutes of each stage.

[0041] Example 5

[0042] Preparation of wood materials: The wood is crushed into 20 mesh particles and the moisture content is controlled at 12%.

[0043] Modal fiber preparation: treated with aluminate coupling agent, the amount used is 1.0% of the fiber mass.

[0044] Embryo assembly and gluing: The mass ratio of wood material to modal fiber is 4:1. The wood particles and modal fibers are laid alternately in layers. Each layer is sprayed with phenolic resin glue. The amount of phenolic resin glue is 75Kg / m 3 .

[0045] Cold pressing treatment: pressure 1.8MPa, time 24 hours, ambient temperature 25℃, humidity 55%. Micro-vibration was applied during the pressure increase and final pressure stages, with a frequency of 30 Hz and an amplitude of 0.3 mm, and the time was the last 15 minutes of each stage.

[0046] Performance testing steps

[0047] The plywood prepared in each example was measured and its thickness, length and width were recorded.

[0048] The flexural strength and elastic modulus of plywood were tested using a universal material testing machine.

[0049] To conduct a water resistance test, the plywood was immersed in water and its water absorption and expansion rate were recorded at different time points.

[0050] Weathering tests are conducted to simulate the effects of different climatic conditions on plywood and observe its surface changes and performance degradation.

[0051] 1. Ultraviolet exposure test:

[0052] Exposure time: The exposure time is 1000 hours.

[0053] UV intensity: 70℃, 0.55W / m 2 .

[0054] 2. Salt spray corrosion test:

[0055] Spray time: Set the total spray time to 240 hours.

[0056] Spray volume: set to 500mL / m per hour 2 .

[0057] Salt solution concentration: 5% NaCl solution.

[0058] 3. Thermal stability test:

[0059] High temperature condition: set to 100°C, duration 48 hours.

[0060] 4.Wet heat cycle test:

[0061] High temperature and high humidity conditions: The temperature is set at 60°C, the humidity is 95%, and each cycle lasts for 24 hours.

[0062] Number of cycles: 10 cycles were performed.

[0063] Star rating criteria:

[0064] Appearance changes:

[0065] 5 stars: No visible changes.

[0066] 4 stars: Slight color change, no cracks or deformation.

[0067] 3 stars: Moderate color variation, slight cracking may occur.

[0068] 2 stars: Obvious color change, cracks or slight deformation.

[0069] 1 star: Severe color change, obvious cracks or deformation.

[0070] Performance indicators:

[0071] The rating is based on the change in performance indicators before and after the experiment (such as tensile strength, compressive strength, etc.). Performance degradation within 5% is 5 stars, 5-10% is 4 stars, 10-20% is 3 stars, 20-30% is 2 stars, and more than 30% is 1 star.

[0072] Overall rating:

[0073] Combine the appearance changes and performance indicators to give a comprehensive star rating. For example, if both are 5 stars, the comprehensive rating is 5 stars, and so on.

[0074] Table 1. Comprehensive performance comparison

[0075]

[0076] The processing performance of plywood is tested, including cutting and drilling, to evaluate the difficulty and tool wear during processing. The following tests are performed:

[0077] 1. Material preparation:

[0078] The boards prepared in Examples 1-5 and commercially available ordinary plywood were prepared as controls; cutting blades and drill bits of the same type were prepared.

[0079] 2. Cutting experiment:

[0080] Cut all samples using the same cutting parameters (speed, depth, etc.). Record the cutting time and the quality of the cut surface (flatness, burrs, etc.) for each sample. Measure the wear of the blade after cutting.

[0081] 3. Drilling experiment:

[0082] Drill all samples under the same drilling parameters (speed, feed rate, etc.). Record the drilling time and the quality of the hole (smoothness, hole diameter accuracy). Measure the wear of the drill bit.

[0083] 4. Material loss measurement:

[0084] During the processing, the material loss of each sample is collected and recorded.

[0085] 5. Data recording and analysis:

[0086] All experimental data are recorded in Table 2. Compare and analyze the differences in processing performance of different samples.

[0087] Table 2. Processing performance comparison data

[0088]

Claims

1. A process for producing plywood containing modal fibers, characterized in that: The preparation steps are: Preparation of wood materials: crush the wood into particles not exceeding 30 mesh, and control the moisture content of the wood between 8% and 12%; Modal fiber preparation: spray the modal fiber with coupling agent or use steam explosion treatment, the amount of coupling agent used is 0.1%-2.0% of the modal fiber mass; Embryo assembly and gluing: According to the mass ratio of wood material: modal fiber (90-70): (30-10), the wood particles and modal fiber are laid alternately in layers, and phenolic resin glue is sprayed on each layer. The amount of phenolic resin glue is 70-100 kg / m 3 ; Cold pressing treatment: The cold pressing pressure is controlled between 1.2-1.8MPa, the pressing time is set to 12-24 hours, the pressing environment temperature is 20-25℃, the humidity is 45%-55%, and vibration assistance is implemented during the pressing process; Depressurization and removal: After pressing is completed, depressurize and remove the plywood.

2. The process for producing plywood containing modal fiber according to claim 1, characterized in that: The coupling agent is an aluminate coupling agent, and the phenolic resin adhesive is an LPF resin adhesive.

3. The process for producing plywood containing modal fiber according to claim 1, characterized in that: The steam explosion treatment method is as follows: the modal fiber is crushed to less than 30 meshes, soaked in a 2wt.% NaOH solution, and then the modal fiber is placed in a closed steam explosion chamber, the steam pressure is controlled at 1.0~7.0MPa, and the fiber is treated in high-temperature and high-pressure steam for 15~40 seconds; the pressure is completely released within 0.00875 seconds, and the fiber is cleaned with ethanol.

4. The process for producing plywood containing modal fiber according to claim 3, characterized in that: After the steam pressure rises to 7.0 MPa, it is maintained for 4 to 5 seconds.

5. The process for producing plywood containing modal fiber according to claim 1, characterized in that: The mass ratio of the wood material to the modal fiber is 4:

1.

6. The process for producing plywood containing modal fiber according to claim 2, characterized in that: The amount of LPF resin adhesive is 75Kg / m 3 .

7. The process for producing plywood containing modal fiber according to claim 1, characterized in that: The initial stage of the cold pressing: starting with a pressure of 0.5-0.8 MPa, the duration is 20%-30% of the total pressing time; the pressure increasing stage: increasing the pressure to 1.4-1.5 MPa, the duration is 40%-50% of the total pressing time; the final pressing stage: during the remaining part of the pressing time, the pressure is increased to 1.6 MPa.

8. The process for producing plywood containing modal fiber according to claim 1, characterized in that: The parameters of the cold pressing treatment are: the pressure is controlled at 1.5 MPa, the pressing time is set to 18 hours, the ambient temperature is controlled at 22-24° C., and the humidity is controlled at 48%-52%.

9. The process for producing plywood containing modal fiber according to claim 1, characterized in that: The vibration frequency: micro-vibration is applied in the pressure-increasing stage and the final pressure stage, and the vibration frequency is controlled between 10-50 Hz; vibration amplitude: the vibration amplitude of micro-vibration is controlled between 0.1-0.5 mm; vibration time: micro-vibration is applied within the last 10-15 minutes of each pressing stage.

10. Plywood containing modal fibers obtained by the production process according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for producing paperboards and paper tubes

    CN102248562A

  • Manufacturing method of formaldehyde-free plant fiber packaging materials

    CN102268847A

  • Composite floor and production method thereof

    CN103362288A

  • Environment-friendly plate for custom furniture production and manufacturing method of environment-friendly plate

    CN105415477A

  • Production method of reinforced waterproof board and production method of reinforced waterproof decorative board

    CN105882046A